The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fphar.2022.927653
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in pathogenesis, diagnosis, and treatment of pulmonary fibrosis

Abstract: Pulmonary fibrosis (PF) is a group of interstitial lung diseases that seriously endanger human life and health. Despite the current advances in research on the pathogenesis and treatment of PF, the overall quality of survival and survival rates of PF patients remain low, prompting the search for more effective therapeutic approaches. Exosomes are nanoscale vesicles with diameters ranging from approximately 30–150 nm, capable of transporting a variety of molecules in the body and mediating intercellular communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…The endosome buds inwardly and captures specific cytoplasmic molecules that lead to the creation of intraluminal vesicles (ILVs) (Figure 2). 36 The ESE is a relatively “large vesicle” and the primitive membrane site, created by the merger of endocytic vesicles containing the tubular extension, which is developed by RAB5, RAB4, RAB7, RAB11, retromer, and caveolae‐1 molecules 43 . The endocytic vesicles are constructed by clathrin‐mediated endocytosis (CME) or clathrin‐independent (CIE) ways 44 .…”
Section: Exosomes Characteristics and Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The endosome buds inwardly and captures specific cytoplasmic molecules that lead to the creation of intraluminal vesicles (ILVs) (Figure 2). 36 The ESE is a relatively “large vesicle” and the primitive membrane site, created by the merger of endocytic vesicles containing the tubular extension, which is developed by RAB5, RAB4, RAB7, RAB11, retromer, and caveolae‐1 molecules 43 . The endocytic vesicles are constructed by clathrin‐mediated endocytosis (CME) or clathrin‐independent (CIE) ways 44 .…”
Section: Exosomes Characteristics and Biogenesismentioning
confidence: 99%
“… 36 The ESE is a relatively “large vesicle” and the primitive membrane site, created by the merger of endocytic vesicles containing the tubular extension, which is developed by RAB5, RAB4, RAB7, RAB11, retromer, and caveolae‐1 molecules. 43 The endocytic vesicles are constructed by clathrin‐mediated endocytosis (CME) or clathrin‐independent (CIE) ways. 44 A part of sorted endosomes may revert to the membrane via “Fast recycling” or “Slow recycling” to recuperate vesicles.…”
Section: Exosomes Characteristics and Biogenesismentioning
confidence: 99%
“…Exosomes are phospholipid bilayer membranous vesicles, measuring between 30 and 150 nm ( Negrete-Garcia et al, 2022 ). Continuously secreted by a variety of cell types, they transport biologically active substances such as proteins, lipids, and genetic material (DNA, mRNA, miRNAs, and lncRNAs) ( Yang et al, 2022 ). Bronchial epithelial cells primarily generate exosomes in the lungs, which activate fibroblasts, stimulate their differentiation into myofibroblasts, and catalyze excessive extracellular matrix component deposition ( Abreu et al, 2021 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Hypoxia in the tumor microenvironment (TME) is closely associated with cancer progression, metastasis, and mortality . Some research reports have shown that the high metastasis rate of HCC is not only determined by the malignant potential of HCC itself but is also caused by the signals of TME . However, the specific underlying molecular mechanisms have not been elucidated from both biological and physical perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some research reports have shown that the high metastasis rate of HCC is not only determined by the malignant potential of HCC itself but is also caused by the signals of TME. 6 However, the specific underlying molecular mechanisms have not been elucidated from both biological and physical perspectives. An exosome is an extracellular vesicle and is secreted by a cell.…”
Section: ■ Introductionmentioning
confidence: 99%